Book Reviews. Issue 3 (1st September 2018) - Stilley, Harriet; Weston, Daniel; Dillon, Ellen; Dean, Tim; Fagan, Calvin; Jones, Nick; Kardux, Johanna C.; King, Amy K.
Contemporary Masculinities in Fiction, Film and Television, Brian Baker (2015) New York: Bloomsbury, 272 pp., ISBN 9-781-62356-747-7, h/bk, £86.40, p/bk, £28.79Imagining Extinction: The Cultural Meanings of Endangered Species, Ursula K. Heise (2016) Chicago and London: University of Chicago Press, 280 pp., ISBN 978-0-22635-816-1, p/bk, £20.50Staying with the Trouble: Making Kin in the Chthulucene, Donna Haraway (2016) Durham, NC and London: Duke University Press, 312 pp., ISBN 9-780-82236-224-1, p/bk, £19.99, $26.95The War on Sex, David M. Halperin and Trevor Hoppe (eds) (2017) Durham, NC and London: Duke University Press, xi + 497 pp., ISBN 9-780-82236-367-5, p/bk, £23.99, $31.95The Hollywood War Film: Critical Observations from World War I to Iraq, Daniel Binns (2017) Bristol: Intellect, 172 pp., ISBN 9-781-78320-754-1, p/bk, £32.50, $43The Imaginary Geography of Hollywood Cinema 1960–2000, Christian B. Long (2017) Bristol and Chicago: Intellect, 291 pp., ISBN 9-781-78320-829-6, h/bk, £70.00Moby-Dick and Melville's Anti-Slavery Allegory, Brian R. Pellar (2017) Basingstoke: Palgrave Macmillan, 234 pp., ISBN 9-783-31952-266-1, h/bk, £67.99Being Ugly: Southern Women Writers and Social Rebellion, Monica Carol Miller (2017) Baton Rouge: Louisiana State University Press, 176 pp., ISBN 9-780-80716-560-7, h/bk, £30.00